133k views
4 votes
(50k³ + 10k² − 35k – 7) ÷ (5k − 4)How do I simplify this problem

User Prostock
by
5.4k points

1 Answer

4 votes

ANSWER :


10k^(2)+10k+1-(3)/(5k-4)

EXPLANATION :

From the problem, we have an expression :


(50k^3+10k^2-35k-7)/(5k-4)

The divisor is (5k - 4)

Step 1 :

Divide the 1st term by the first term of the divisor.


(50k^3)/(5k)=10k^2

The result is 10k^2

Step 2 :

Multiply the result to the divisor :


10k^2(5k-4)=50k^3-40k^2

Step 3 :

Subtract the result from the polynomial :


(50k^3+10k^2-35k-7)-(50k^3-40k^2)=50k^2-35k-7

Now we have the polynomial :


50k^2-35k-7

Repeat Step 1 :


(50k^2)/(5k)=10k

The result is 10k

Repeat Step 2 :


10k(5k-4)=50k^2-40k

Repeat Step 3 :


(50k^2-35k-7)-(50k^2-40k)=5k-7

Now we have the polynomial :


5k-7

Repeat Step 1 :


(5k)/(5k)=1

The result is 1

Repeat Step 2 :


1(5k-4)=5k-4

Repeat Step 3 :


(5k-7)-(5k-4)=-3

Since -3 is a number, this will be the remainder.

Collect the bold results we had from above :

(10k^2 + 10k + 1) remainder -3

Note that the remainder can be expressed as remainder over divisor.

That will be :


\begin{gathered} 10k^2+10k+1+(-3)/(5k-4) \\ or \\ 10k^2+10k+1-(3)/(5k-4) \end{gathered}

User Enavuio
by
4.5k points